Cardiac arrest in the workplace and its outcome: a systematic review and meta-analysis. (November 2015) - Descatha, Alexis; Dagrenat, Céline; Cassan, Pascal; Jost, Daniel; Loeb, Thomas; Baer, Michel
Abstract: Introduction: Out-of-hospital cardiac arrest (OHCA) in the workplace appears to be managed more effectively than OHCA occurring in other places. A systematic review and meta-analysis of the available epidemiological data was performed, comparing the rate of survival for OHCA in the workplace, versus survival in other locations. Methods: Four databases (Pub-Med, Scopus, Web of science, "Base de Données de Santé Publique", BDSP, i.e. the French Public Health Database) were searched from 01/2000 to 03/2015, using the key words: ("Cardiac arrest") and ("occupational" OR "workplace" OR "public location"). A two stage process with two independent readers was used to select relevant papers. Numbers of subjects who suffered from OHCA in the workplace versus other locations were extracted when possible, as well as their respective outcomes (admitted alive to the hospital, discharged alive, good neurological outcome). Metarisks were calculated using the generic variance approach (meta-odds ratios metaOR). Results: After full-text reading, 17 papers were included, from 9 countries, mostly published after 2005, and coming mostly from prospective registers. "Workplace" was defined differently in different studies, mostly in terms of industrial sites and offices. The workplace was an exceptional location for occurrences of OHCA (from 0.3% to 4.7% of all OHCA, from 1.3 to 23.8 events per million people per year), based on 2077 OHCA. In the quantitative analyses (survival available, 10 studies), MetaOR were found to be relatively consistent and high (from 1.9 (1.5–2.3) to 5.9(2.7–13.0)). When OHCA occurring at workplaces were compared to other public sites, no significant differences were found. Conclusion: There is sufficient evidence to support the view that there will be better outcomes for OHCA cases that occur in the workplace than for those occurring elsewhere. Requirements for occupational health and safety should include prevention of such major (albeit rare) events.